2015
DOI: 10.1134/s107042801505022x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of new benzo[4,5]thiazolo[3,2-a]pyrimidine derivatives

Abstract: Heating a mixture of substituted malonic esters and 6-methoxy-1,3-benzothiazolyl-2-amine afforded new derivatives of benzo [4,5]thiazolo[3,2-a]pyrimidine, 3-substituted 2-hydroxy-4Н-benzo[4,5]thiazolo[3,2-a]pyrimidine-4-ones. The choice between the possible tautomers was carried out basing on the Xray diffraction analysis of 3-formyl-2-chloro derivative synthesized by formylation of unsubstituted heterocycle by Vilsmeier reaction.The interest to the synthesis and investigation of derivatives of fused pyrimidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A variety of effective strategies for the synthesis of pyrimido [2,1-b] [1,3]benzothiazole and [1,3]benzothiazolo [3,2-a]quinazoline derivatives have therefore been reported in literature. Most of the methods depict syntheses of pyrimido[2,1-b] [1,3]benzothiazole and [1,3]benzothiazolo [3,2-a]quinazoline derivatives from intermolecular cyclization of 2-aminobenzothiazoles with malonic ester derivatives, 2,12 Meldrum's acid, 13 and β-ketoesters. 14 The reaction of 2-aminobenzothiazoles with various Michael acceptors, such as acetylenic compounds, 15,16 alkyl malonates, 8,17 and enaminones.…”
Section: Quinazoline Moietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of effective strategies for the synthesis of pyrimido [2,1-b] [1,3]benzothiazole and [1,3]benzothiazolo [3,2-a]quinazoline derivatives have therefore been reported in literature. Most of the methods depict syntheses of pyrimido[2,1-b] [1,3]benzothiazole and [1,3]benzothiazolo [3,2-a]quinazoline derivatives from intermolecular cyclization of 2-aminobenzothiazoles with malonic ester derivatives, 2,12 Meldrum's acid, 13 and β-ketoesters. 14 The reaction of 2-aminobenzothiazoles with various Michael acceptors, such as acetylenic compounds, 15,16 alkyl malonates, 8,17 and enaminones.…”
Section: Quinazoline Moietiesmentioning
confidence: 99%
“…Fused pyrimidines heterocyclic compounds are ubiquitous in natural products, drug molecules, and functional materials. 1 Among them, especially pyrimido [2,1-b] [1,3]benzothiazole and [1,3]benzothiazolo [3,2a]quinazoline derivatives have been related to an extensive range of pharmacological activities, such as antibacterial A, 2 antimicrobial B, 3 antiallergy C, 4 antifungal D, 5 anticancer E, 6 antihistaminic F, 7 anticonvulsant G, 8 and anti-inflammatory activity H (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have developed a fundamentally new method of constructing the derivatives of the heterocyclic system of benzo [4′,5] imidazo[2′,1′:6,1]pyrido [2,3-d]pyrimidine [1], which allowed the introduction of methyl and methylene into the molecule groups. It should be noted that some derivatives of the indicated heterocyclic system revealed antibacterial and ant monoamine oxidase properties [2,3]. Taking into account, we have developed possibilities for the further functionalization of the class of compounds under discussion, in particular, for obtaining new derivatives on their basis with a lengthy system of conjugated π-bonds that are interesting in terms of biomedical and technical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Only Patel and co-workers reported that the compounds bearing the 4 H -benzo­[4,5]-thiazolo­[3,2- a ]­pyrimidine moiety could be used as antimycobacterial and antioxidant agents (Figure ). The existing synthetic methods for this kind of compound only include (i) the synthesis of 3-substituted 2-hydroxy-4 H -benzo­[4,5]-thiazolo­[3,2- a ]­pyrimidine-4-ones by the reactions of substituted malonic esters and 6-methoxy-1,3-benzothiazolyl-2-amine at 200 °C, (ii) the microwave-assisted synthesis of ethyl 2-methyl-4-(pyridin-2-yl)-4 H -benzo­[4,5]­thiazolo­[3,2- a ]­pyrimidine-3-carboxylates by the reactions of 2-aminobenzothiazoles with pyridine-2-aldehyde and ethyl acetoacetate in the presence of PdCl 2 as an expeditious catalyst, , and (iii) the synthesis of 2,4-diaryl-6,7,8,9-tetrahydro-4 H -benzo­[4,5]­thiazolo­[3,2- a ]­pyrimidine hydrobromides by the α-bromination of cyclohexanone with N -bromosuccinamide (NBS), followed by cyclization with 3,4-dihydropyrimidine-2­(1 H )-thiones in the presence of p -toluenesulfonic acid (PTSA) (Scheme ). However, some drawbacks still remain for these methods, such as the use of a very high temperature, the use of noble transition metal as a catalyst, the limited product examples, etc.…”
mentioning
confidence: 99%